Synergistic engineering of defects and architecture in CoFe@NC toward highly eﬃcient oxygen electrode reactions. (18th March 2020) - Wang, Ying; Hu, Tianjun; Qiao, Yanting; Chen, Yan
Abstract: An efficient synthesis method combining the advantages of defect and surface structure engineering is present to prepare oxygen electrode materials with a unique nanoarchitecture (namely, CoFe@NC heterostructures, for which lattice-dislocated CoFe alloy nanoparticles encapsulated in nitrogen-doped carbon layers). The CoFe@NC heterostructures provide an abundance active sites and are found to exhibit dramatically improved electrocatalytic activity for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). With the advantages of unique hierarchical nanostructure, the presence of crystal lattice dislocations of CoFe alloy and the synergistic effect between CoFe alloy and carbon layers, the CoFe@NC exhibits good performances for ORR and OER with the overpotential of 770 mV when used as bifunctional catalyst, much smaller than other reported electrocatalysts, suggesting the CoFe@NC is a promising candidate as an efficient bifunctional catalyst for fuel cells and metal-air batteries. Highlights: The CoFe@NC were synthesized by a convenient strategy. The CoFe@NC exhibits good bifunctional catalytic activity for ORR and OER. The defect structure and the interaction between alloy and carbon improve activity.